The novel metallo‐β‐lactamase PNGM‐1 from a deep‐sea sediment metagenome: crystallization and X‐ray crystallographic analysis. Issue 10 (3rd October 2018) - Park, Kwang Seung; Hong, Myoung-Ki; Jeon, Jin Wan; Kim, Ji Hwan; Jeon, Jeong Ho; Lee, Jung Hun; Kim, Tae Yeong; Karim, Asad Mustafa; Malik, Sumera Kausar; Kang, Lin-Woo; Lee, Sang Hee
Abstract : Metallo‐β‐lactamases (MBLs) may hydrolyze the β‐lactam rings of antibiotics. PNGM‐1 is a subclass B3 deep‐sea sediment MBL that predates the antibiotic era. Crystals of native and selenomethionine‐substituted PNGM‐1 diffracted to 2.1 and 2.3 Å resolution, respectively. They belonged to space group P 21 and probably contain 6–10 molecules in the crystallographic asymmetric unit. Abstract : Metallo‐β‐lactamases (MBLs) are present in major Gram‐negative pathogens and environmental species, and pose great health risks because of their ability to hydrolyze the β‐lactam rings of antibiotics such as carbapenems. PNGM‐1 was the first reported case of a subclass B3 MBL protein that was identified from a metagenomic library from deep‐sea sediments that predate the antibiotic era. In this study, PNGM‐1 was overexpressed, purified and crystallized. Crystals of native and selenomethionine‐substituted PNGM‐1 diffracted to 2.10 and 2.30 Å resolution, respectively. Both the native and the selenomethionine‐labelled PNGM‐1 crystals belonged to the monoclinic space group P 21, with unit‐cell parameters a = 122, b = 83, c = 163 Å, β = 110°. Matthews coefficient ( V M ) calculations suggested the presence of 6–10 molecules in the asymmetric unit, corresponding to a solvent content of ∼31–58%. Structure determination is currently in progress.